Relative Frequency of 35delG Mutation in GJB2 Gene in Autosomal Recessive Non-Syndromic Hearing Loss (ARNSHL) Patients in Kerman Population - N Bazazzadegan; N Mirhoseini; H Ziaaddini; AR Asadi; K Kahrizi; S Arzhangi; A Astani; M Mohseni; Y Riazalhosseini; M Nejat; Kh Jalalvand; RJH Smith; et al. (Journal of Kerman University of Medical Sciences, 2004)
Congenital hearing loss with many genetic and environmental causes affects 1 in 1000 newborns. Mutations in the GJB2(Gap Junction Beta-2) gene encoding the gap junction protein connexin 26 have been established as the main cause of autosomal recessive non-syndromic hearing loss. The aim of this study was to study the frequency of one mutation (35delG) of GJB2 gene in Kerman non-syndromic deaf population. For this purpose, 130 chromosomes from 65 patients were studied and 35delG mutation was diagnosed in 3(2.3%) chromosomes (one patient was homozygote and the other one was heterozygote). This rate of frequency is significantly higher comparing to that in the whole population of Iran.